Integrating bioplastics into the US plastics supply chain: towards a policy research agenda for the bioplastic transition - Shah, Kalim U.; Gangadeen, Isaiah (Frontiers in Environmental Science, 2023)
Bioplastics have the potential to fill the role of conventional plastics but with lowered environmental and ecological impacts. But bioplastic production suffers from high production costs and as an immature technology, it proves less competitive than its petrol-based counterpart. Debates about the social versus private benefits of bioplastics are also cited. The literature argues that various biofeedstock sources can produce high-quality drop-in plastics and that scaling up bioplastic production will provide the cost competitiveness needed to transition away from petroplastics. However, the market remains uncoordinated and lacks a strategic and comprehensive plan for the plastic transition. Moreover, the science-to-policy literature on bioplastics is very limited, providing scarce evidence or analysis to policy makers attempting to argue for bioplastics industrialization and integration. In this study we highlight this missing link particularly in the North American context in order to encourage further inquiry on these matters. Using Stern's policy framework gap analysis approach, our evaluation identifies gaps in existing policy frameworks pertinent to bioplastics supply chains. On this basis we identify and prioritize five pointed areas for policy focus to advance bioplastics sector growth and integration. These are developing a strategy to sustainably coordinate and promote biomass production; incentivizing bioplastic investments and production; incentivizing bioplastic substitution; and enhancing the end-use management. Additionally, research is needed to support the technical performance of bioplastics, industrialization methods, supply chain integration, and the impact of exogenous factors.